2022
DOI: 10.1186/s12955-022-01968-0
|View full text |Cite
|
Sign up to set email alerts
|

The association between health-promoting-lifestyles, and socioeconomic, family relationships, social support, health-related quality of life among older adults in china: a cross sectional study

Abstract: Objectives Lifestyles, accounting for 53% in determining death, play a vital role in improving the health of older adults. Thus, this study aimed to explore the influencing factors of the health-promoting-lifestyles and interaction mechanisms among older adults. Methods A total of 8526 elders were selected by a three-stage stratified random cluster sampling method. Socioeconomic status, family relationships, social support, health-related quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 33 publications
3
16
0
1
Order By: Relevance
“…That is the reason could explain that the self-care abilities, healthpromoting lifestyles and HRQOL level were poor in the Bai subjects. Our study was consistent with some previous researches, in which they also reported older age and education are the associated factors with hypertension [28,29].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…That is the reason could explain that the self-care abilities, healthpromoting lifestyles and HRQOL level were poor in the Bai subjects. Our study was consistent with some previous researches, in which they also reported older age and education are the associated factors with hypertension [28,29].…”
Section: Discussionsupporting
confidence: 94%
“…So we found the HPLP grades were positively correlated with their ESCA and HRQOL level, which meant the higher scores of the HPLP scales, the better the self-care abilities and health-related quality of life are available to the elderly. This nding was consistent with the study of Zheng et al [29] which also implied that better HPLP was associated with higher QOL. Therefore, it is important to educate the sampling population to adhere to the recommended lifestyle to help them control their blood pressure and attain better HRQOL.…”
Section: Discussionsupporting
confidence: 93%
“…So we found the HPLP-II grades were positively correlated with their ESCA and HRQOL levels, which meant the higher scores of the HPLP-II scales, the better the self-care abilities and health-related quality of life are available to the older adults. This finding was consistent with the study of Zheng et al [28] which also implied that better HPLP-II was associated with higher QOL. Therefore, it is important to educate the sampling population to adhere to the recommended lifestyle to help them control their blood pressure and attain better HRQOL.…”
Section: Discussionsupporting
confidence: 93%
“…Good family functioning promotes the maintenance and integrity of psychological and physical health of older people, ensuring well-being, social support and health-promoting life styles 19,20 . Amid the pandemic, it is assumed that older people whose family relationships were impacted received poorer or no social support.…”
Section: Introductionmentioning
confidence: 99%